Precision manufacturing using additive manufacturing - Ohlsson, Martin; Pasupulate Suresh, Akshaykumar (My University, 2021)
Additive Manufacturing can be used for additive manufacturing complex parts with limitations to size of the feature and capability of the machine. There exist several technologies for metal additive manufacturing but this project focuses its case study on the laser based powder bed fusion process. In order to find the geometrical deviation and variation for the small features, artifact models were designed, printed and analyzed. Ten different prints were done in order to analyse the geometrical deviation of the features different process parameters. A measurement strategy is introduced in the thesis to standardize measurement procedure to reduce the errors. A comparison between the different measuring techniques with their advantages and disadvantages are mentioned for the case study. Finally, a comparison between the parts printed using LB-PBF and Binder Jetting was done. All the results provided are subject to the scope of the project and provides a learning outcome to carry out the future research. The results indicate that the orientation of the features with respect to the recoater and the setting of amount of gas flow and its direction has an effect on the accuracy of the parts. From the analysis, the least deviation is achieved using 65% gas flow in relation to standard settings for most of the features. These results can be verified and concluded only with the further investigations. There is a high possibility for the bending of arrows of the waveguide in the first and the last positions when additive manufactured. The selection of measurement technique and strategies based on the feature size and shape is important and the human error during measurements is dependent on the magnification of the measuring instrument and has to be selected wisely. A human error of 3 to 5 μm during measurements was seen in this thesis project. From the electrical evaluation of waveguide, it was seen that there is a repeatability and geometrical accuracy for the prints 3, 4 and 5.
Keywords: Accuracy; Additive manufacturing; Artifact; Binder Jetting; Deviation; Dimensions; Geometrical Accuracy; Measurements; Strategy; Variation; LB-PBF